Business librarianship and inforamation[sic] services : proceedings of the IIML-MANLIBNET, 3rd annual National Convention held at Indian Institute of Management, Lucknow, during March 12-14, 2001 - MANLIBNET (Network). National Convention. 2001 : Lucknow, India); Raina, Roshan; Malhan, Inder Vir, 1954-; MANLIBNET (Network); Indian Institute of Management, Lucknow (Lucknow : International Book Distributing Co., 2002)
Contributed articles presented at the 3rd annual National Convention of MANLIBNET.
Includes bibliographical references and indexes.
Keywords: Libraries -- India -- Automation -- Congresses; Library information networks -- India -- Congresses..; Information science -- Technological innovations -- India -- Congresses